Evaluación de un medio de cultivo para diferenciar cepas vacunales de Salmonella de aislamientos de campo - Joaquim, Patricia Estefania; Arenas Mosquera, David José; Albarracín, Brenda; Sanow, Rocio Belen; Chacana, Pablo (Asociación Argentina de Microbiología, 2024)
Poster